WASTE MANAGEMENT IN THE CONTEXT OF ENVIRONMENTAL MODERNIZATION OF COMMUNITY DEVELOPMENT (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. The article considers topical issues of ecological modernization of socio-economic development of territorial communities. Emphasis is placed on the need for close implementation of environmental issues, prevention of environmental degradation, ensuring a high level of environmental security and increasing the investment attractiveness of communities through the rational use of environmental factors of social and economic development.The purpose of the article is to substantiate the directions of ecological modernization of the development of territorial communities of Ternopil region by improving the system of waste management and waste management at the local level.Research methods. Methods of systematic, structural-logical analysis and generalization were used in the preparation of the scientific publication.Results. The problem of solid waste generation and accumulation has now become one of the key issues in the environmental modernization of community development in Ukraine. The article considers the reasons for this situation, analyzes the state and development of waste management and management in the Ternopil region. The causes, consequences and territorial differences in the effectiveness of solving this problem on the ground have been identified, limiting factors have been identified that do not allow to fully solve the problem of waste accumulation in the region, prevent their negative impact on the environment and public health.Based on the analysis and identified problems in the field of waste management, the main directions of reforming the waste management system in territorial communities of Ternopil region, increasing the environmental investment attractiveness of their territories, reducing the risks of environmental threats associated with solid waste accumulation are proposed. including through the involvement in the production of secondary raw materials.